(untitled) (Bangladesh Journal of Medical Science, 2024)
Introduction Breast cancer is the most common cancer, accounting for 38.9% of all cancers diagnosed, it is also the most fatal among Moroccan women. The aims of this study were to draw up an epidemiological profile of breast cancer and to establish the link between patient characteristics and the histological types of cancer observed. Methods This was a retrospective study including 877 patients with histologically confirmed breast cancer. The study was conducted at the Reproductive Health Reference Center in the province of Kénitra (Morocco). It covered the period 2013 - 2018. Results The median age of patients at diagnosis was 50 years (Q1-Q3: 42 - 58 years). Most patients were aged 40 years or older (84.04%) and married (67.32%). They were nulliparous in 18.61% of cases. The average number of live children (LVC) was 3.5 LVC (Q1- Q3: 2 - 5 LVC). Approximately 10.22% of patients had a family history of invasive carcinoma (96.58%). The median tumour size was 25 mm (Q1 - Q3: 20 - 36 mm). The predominant histological type was invasive ductal carcinoma. The most common Scarff- Bloom-Richardson (SBR) grade was SBR II (63.64%). High histological grade correlated with large tumour size. Histological type showed a significant association with time to consultation (p<0.05) and age at first pregnancy (p<0.05). Conclusion All the contextual factors need to be taken into account to improve the assessment of the risk of developing breast cancer, and even of dying from it. Research, awareness-raising and ongoing education are essential if we are to develop more effective prevention strategies and treatments. Bangladesh Journal of Medical Science Vol. 23 No. 04 October’24 Page : 1129-1136